Physical violence cases in Pekanbaru, Indonesia: a 5 years retrospective study - Dedi Afandi (Majalah Kedokteran Andalas, 2018)
Violence is a global public health problem. This study aims to identify the prevalence and patterns of injury among physical violence victims in Pekanbaru, Indonesia. Methods: A retrospective descriptive study was conducted at the Forensic Medical Service Center Bhayangkara Hospital Pekanbaru. All medicolegal reports of physical violence victims from January 1, 2010 to December 31, 2014 were studied for the prevalence of physical violence cases using basic data, such as sex, age, occupation, and forensic examination findings. Results: The average prevalence of sexual violence was 51.47/100,000 population/year. The total number of cases was 5,206, of which 75.7% were males. The 18-34-year-old age groups accounted for the highest proportion of cases for both genders. Bruises and abrasions were the most frequently found injuries (67.8% and 57.3%, respectively), with the head being the most common injury sites. The majority of victims had blunt and mild degree of injuries (85.6% and 83.8%, respectively). Conclusions: the prevalence of physical violence cases was high among study populated. Although most of the victims had non-fatal injury but physical violence can affect all age group and both genders.